Comparison of Extracted Haar Wavelet Features for Herbal Leaf Type Classification - Jusman Yessi; Arisandy Kusumaning Putri Arif; Nur Nazilah Chamim Anna; Ardiyanto Yudhi (E3S Web of Conferences)
Plants are incredibly beneficial to human survival in various ways. Leaves are part of plants widely used as medicine. They are similar in shape but have different advantages. Leaf types can only be identified by experts. This study aims to create a classification system for herbal leaves based on the Haar wavelet transform and machine learning. The study was carried out to assist ordinary people in recognizing herbal leaves. The results revealed that Haar wavelet level 1 was better suited to the leaf data. The Quadratic SVM model yielded the highest result with an accuracy of 77%, a precision of 83%, a recall of 83%, a specificity of 82%, and an F-score of 73%.